Soil Carbon Sequestration and Nutrient Status of Rice-Based Cropping Systems: A Case Study from Mymensingh District in Bangladesh - Sabina Yeasmin; Md. Mizanur Rahman; Ahmed Khairul Hasan; A. K. M. Mominul Islam; Md. Parvez Anwar (Fundamental and Applied Agriculture)
Carbon (C) sequestration in soil plays a crucial role in increasing soil quality through recommended management practices including applying organic amendments, following cropping patterns, fallow periods etc. This study aimed to assess the influence of rice-based cropping patterns on soil C and nutrient status in surface (0-15 cm) and sub-surface soil (15-30 cm). Soils of five rice-based cropping patterns [Boro (winter rice)-Fallow-Fallow, Boro-Fallow-Aman (monsoon rice), Boro-Fallow-Aman-Mustard, Boro-Aus (summer rice)-Aman, Vegetables-short Fallow-Aman] from farmers' fields of Mymensingh district in Bangladesh were collected. Bulk soils were physically fractionated into particulate organic matter (POM: >53 µm) and mineral associated OM (MOM: < 53 µm) to assess the organic C (OC) distribution. Bulk soils were analyzed for soil pH, electrical conductivity, soil texture, nutrients (OC, nitrogen (N), phosphorus (P), potassium (K) and sulphur (S)) contents. The results showed that all studied parameters varied significantly among the cropping patterns and soil depths. Surface soils contain higher amount of OC, N, P, K and S than sub-surface soils under all rice-based cropping patterns. Overall, relatively higher macronutrients (P, K, S) concentration was found in the cropping patterns with a greater number of crops compared to the patterns including fallow period. In contrast, OC and N were the highest in Boro-Fallow-Fallow field followed by Vegetables-short Fallow-Aman and the rest three patterns, which might correspond to less disturbance of soil. All the rice-based cropping patterns had noticeable proportion of MOM (presumably stable OC) than labile POM which indicates the capacity of paddy soils in sequestering OC in soils. However, this capacity can be influenced by the pattern and probably also by the management systems, e.g., tillage and nutrient managements. These findings revealed the necessity of paying more attention to the selection of cropping pattern and proper land/or crop management for higher C sequestration in arable soil. [Fundam Appl Agric 2024; 9(3.000): 186-194]